QGIS application for spatial and temporal visualisation of data for food safety audits in Malaysia - Kuan, Shuping; Chin, Nyuk Ling; Tee, Tuan Poy; Noor Hasnan, Noor Zafira; Senapi, Mahamad Sukor (Faculty of Medicine and Health Science, Universiti Putra Malaysia, 2023)
Introduction: Advancement in digital technology opens new doors for food safety auditors when it comes to performing food safety audits. Surge of Covid cases since year 2020 has seen an unprecedented switch to remote auditing by the Food Safety and Quality Programme under the arm of Ministry of Health in Malaysia. Methods: This paper presents the use of QGIS, an open-source cross-platform for geographic information system (GIS) to store, manage and visualise 2 types of data, i.e. real time data collected via a mobile device using QField, an open-source mobile application and also fixed data retrieved from existing database. New data from obtained from field sampling and surveillance presents updated information for food safety auditing and enforcement purposes. A total of 4972 datasets were obtained from the Ministry of Health’s Food Safety and Quality Division database on food factories from all 13 states and 3 federal territories in Malaysia. These datasets were transformed and stored into QGIS point layer for performing data classification analysis on clustering of HACCP, GMP and MeSTI certifications. Results: The Penang state has the most HACCP certified companies in fish and fish product category, Selangor is the highest for confectionery industry and Sabah for food services. The general output of mobile GIS provides a big picture of distribution of food safety certifications in Malaysia while more specific adoption of QField can assist in effective field work planning for enforcement officers and auditors leading to cost calculation via information on location, distance and time. Conclusion: QGIS application for spatial and temporal visualisation of data benefits the food safety auditing in Malaysia